2006
DOI: 10.1051/0004-6361:20040294
|View full text |Cite
|
Sign up to set email alerts
|

HCN and HNC mapping of the protostellar core Chamaeleon-MMS1

Abstract: Aims. The purpose of this study is to investigate the distributions of the isomeric molecules HCN and HNC and estimate their abundance ratio in the protostellar core Cha-MMS1 located in Chamaeleon i.Methods. The core was mapped in the J = 1−0 rotational lines of HCN, HNC, and HN 13 C. The column densities of H 13 CN, HN 13 C, H 15 NC and NH 3 were estimated towards the centre of the core. Results. The core is well delineated in all three maps. The kinetic temperature in the core, derived from the NH 3 (1, 1) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 30 publications
2
41
0
1
Order By: Relevance
“…This paper presents a comprehensive analysis of the nature of the core, and gives an overview of previous molecular line and continuum studies of the region. The chemical properties of the core have been also discussed by Kontinen et al (2000) and Tennekes et al (2006). The main conclusion of Belloche et al (2006) is that Cha-MMS1 is not powering the molecular outflow and that it therefore represents either a prestellar core or a transitional object between the prestellar and Class 0 stages.…”
Section: The Cha-mms1 Corementioning
confidence: 85%
“…This paper presents a comprehensive analysis of the nature of the core, and gives an overview of previous molecular line and continuum studies of the region. The chemical properties of the core have been also discussed by Kontinen et al (2000) and Tennekes et al (2006). The main conclusion of Belloche et al (2006) is that Cha-MMS1 is not powering the molecular outflow and that it therefore represents either a prestellar core or a transitional object between the prestellar and Class 0 stages.…”
Section: The Cha-mms1 Corementioning
confidence: 85%
“…The results of these models must then be compared with observations. Although 15 N-substituted species have been observed in a few interstellar sources (e.g., Linke et al 1983;Hermsen et al 1985;Ikeda et al 2002;Tennekes et al 2006), in many cases only weak limits can be placed on the 15 N/ 14 N ratios, in part due to the fact that the lines of the main isotopomer are often optically thick.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in warm dense gas in OMC-1, it is measured to be much smaller than unity (Goldsmith et al 1981(Goldsmith et al , 1986). On the other hand, in cold dense gas, Tennekes et al (2006) derived a somewhat large ratio of 3 − 4 toward Cha-MM1. Colzi et al (2018) showed that for high-mass starless cores, the Schilke et al 1992;Talbi et al 1996).…”
Section: N 2 H + and Ccs Abundancesmentioning
confidence: 95%